Leading in the Digital Era: An MSc Program for Industry 4.0 - Stefani, Antonia; Vassiliadis, Bill; Ntaliakouras, Nikos; Vonitsanos, Gerasimos (Technium Social Sciences Journal, 2023)
In this paper, a new curriculum for an MSc programme is presented. The program is designed to equip students with a deep understanding of the dynamic interplay among automation, data exchange, cloud computing, cyber-physical systems, and the Internet of Things, among other vital components. The curriculum's multifaceted nature ensures that graduates possess the critical thinking, strategic foresight, and interdisciplinary skills essential for leadership in this domain. Social, pedagogical and delivery issues and challenges are discussed.